Ottoman conquests and European ecclesiastical pluralism - Murat Iyigun (Institute for the Study of Labor (IZA), 2006)
This paper emphasizes that the evolution of religious institutions in Europe was influenced by the expansionary threat posed by the Ottoman Empire five centuries ago. This threat intensified in the second half of the 15th century and peaked in the first half of the 16th century with the Ottoman Empire's territorial expansion in Eastern Europe. Various historical accounts have suggested that the Ottomans' rise helped the Protestant Reform movement as well as its various offshoots, such as Zwinglianism, Anabaptism and Calvinism, survive their infancy and mature. In an attempt to conceptualize these effects, I develop a model in which social, cultural or religious affiliation between otherwise heterogenous and conflicting groups can lead to cooperation (at the very least, to a secession of hostilities) when such groups are faced with the threat of potentially stronger rivals of a different affiliation. The overall patterns of conflict in continental Europe as well as those between the Protestant Reformers and the Catholic Counter-Reform movement between the 15th and 17th centuries support the idea that Ottoman military conquests in Europe significantly reduced intra-European feuds.
Keywords: C72; D74; N33; N43; O10; 330; cooperation; conflict; religion; institutions; economic development